Nickel-Catalyzed N-Arylation of Amides with (Hetero)aryl Electrophiles by Using a DBU/NaTFA Dual-Base System - Lundrigan, Travis; Tassone, Joseph P.; Stradiotto, Mark (Synlett, 2021)
The first nickel-catalyzed N-arylation of amides with (hetero)aryl (pseudo)halides employing an organic amine base is described. By using a bis(cyclooctadienyl)nickel/8-[2-(dicyclohexylphosphinyl)phenyl]-1,3,5,7-tetramethyl-2,4,6-trioxa-8-phosphaadamantane catalyst mixture in combination with DBU/NaTFA as a dual-base system, a diversity of (hetero)aryl chloride, bromide, tosylate, and mesylate electrophiles were successfully cross-coupled with structurally diverse primary amides, as well as a selection of secondary amide, lactam, and oxazolidone nucleophiles.
Keywords: nickel catalysis; C–N cross-coupling; amides; arylation